Perancangan Aplikasi Game Edukasi Reaksi Unsur Kimia Menggunakan Metode Linear Congruent Method (LCM) - Muhammad Rinaldi; Ronda Deli Sianturi (JURIKOM (Jurnal Riset Komputer), 2018)
Learning is an activity undertaken by everyone in getting knowledge to face life well. Learning is a "self-generating" necessity of life, which strives for itself, because from the moment human beings have the drive to live their lives. Humans learn continuously to be able to achieve independence and adapt to various environments. The learning of chemical reactions to children should be more joyful and interactive, which can use an interesting song, puzzle, and game media during the learning process. Technology that develops today should be utilized properly because utilizing technology can help and facilitate in various things, especially in terms of learning. One of the fastest growing technologies that can be thought of as a fun lesson is the involvement of games, as the game combines the media of songs, puzzles, and games so that learning becomes fun.